Bitesize has changed! We're updating subjects as fast as we can. Visit our new site to find Bitesize guides and clips - and tell us what you think!

Home > Maths > Geometry > The circle

Maths

The circle

Back

Circle basics

You must be able to recognise when an equation represents a circle.

The general equation of a circle normally appears in the form x^2 + y^2 + 2gx + 2fy + c = 0 where (-g, -f) is the centre of the circle and \sqrt {g^2 + f^2 - c} is the radius.

Notice that for the circle to exist g^2 + f^2 - c > 0.

Look at the following worked examples.

For x^2 + y^2 + 6x - 8y - 11 = 0

g^2 + f^2 - c = (3)^2 + (-4)^2 - ( - 11) = 36

so equation represents a circle with centre (-3, 4) and radius \sqrt {36} = 6

 

For x^2 + y^2 - 2x + 4y + 11 = 0

g^2 + f^2 - c = (-1)^2 + 2^2 - 11 = - 6

so x^2 + y^2 - 2x + 4y - 11 = 0 does not represent a circle.

 

For 3x^2 + 3y^2 - 6x + y - 9 = 0 we must write this starting x^2 + y^2 like this:

\eqalign{ x^2 + y^2 - 2x + {1 \over 3}y - 3 & = & 0\cr\cr g^2 + f^2 - c & = & ( - 1)^2 + ({1 \over 6})^2 - ( - 3) = 4{1 \over {36}} = {{145} \over {36}}\cr

so the equation represents a circle with centre (1, - {1 \over 6}) and radius \sqrt {{{145} \over {36}}} = {{\sqrt {145} } \over 6}

Back

BBC © 2014 The BBC is not responsible for the content of external sites. Read more.

This page is best viewed in an up-to-date web browser with style sheets (CSS) enabled. While you will be able to view the content of this page in your current browser, you will not be able to get the full visual experience. Please consider upgrading your browser software or enabling style sheets (CSS) if you are able to do so.